(untitled) (diségno, 2024)
The use of models in the design process has been a common practice throughout history that still endures. Despite the development of new technologies and their sophisticated ability to represent and anticipate the appearance of architectural designs, physical models continue to captivate us today. Their materiality, combined with their three-dimensionality and the ability to miniaturize architecture as a physical object, still make them an eloquent and irreplaceable communication vehicle. It is difficult to imagine a significant competition where architects reject to present models or photos of them. Here, we analyse the use of models in the design process of Alberto Campo Baeza, their importance in this process, and even the possible influence they exert on his own work. It is necessary to add that models are used in his studio for many different purposes. A detailed analysis of the types of models used by Campo Baeza and their various communicative, expressive, conceptual, and contextualizing purposes is presented here. Also their use as a vehicle for the creative process, testing lighting effects, or as an eloquent tool to be manipulated in order to synthesise and anticipate various aspects of architecture. Throughout this research, a taxonomy of the types and uses of models by this Spanish architect is proposed, delving into the details of their capabilities as project tools.